Using Multivariate Concept-Mapping for Examining Client Understandings of Counselling - Bedi, Robinder P.; Alexander, David A. (Canadian Journal of Counselling and Psychotherapy, 2009)
Many qualitative research methods inadvertently examine the client’s perspective through the lens of researcher- or counsellor-derived constructs and categories, thereby blurring practitioner and client perspectives. This article provides a step-by-step guide for conducting multivariate concept-mapping (MVCM), a mixed-methods research design that can be used to provide more trustworthy accounts of the client’s experience. Until there is a greater accumulation of counselling research using methods that allow clients to categorize the content they provide, this article can serve as an impetus for counsellors to carefully scrutinize the categorization-based research on the client’s perspective that they use to inform their practice.